2014
DOI: 10.1371/journal.pone.0086575
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Membrane-Anchored and Secreted DNA Vaccines Encoding Fatty Acid-Binding Protein and Glutathione S-Transferase against Schistosoma japonicum

Abstract: In order to explore the high performance bivalent DNA-based vaccine against schistosomes, SjFABP and Sj26GST were selected and used to construct a vaccine. Two strategies were used to construct the bivalent DNA vaccine. In the first strategy, a plasmid encoding antigen in the secreted form was used, while in the other, a plasmid encoding a truncated form of SjFABP and Sj26GST targeted to the cell surface was used. Various parameters, including antibody and cytokine response, proliferation, histopathological ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…DNA vaccine is considered an alternative, even optimal approach because of the simplicity of its manufacturing and distribution, biological stability and cost effectiveness [ 31 ]. DNA vaccines have been shown to induce protective immunity against abroad range of pathogens such as Dengue virus [ 32 ], intracellular protozoan Leishmania major [ 33 ] or helminth parasite Schistosoma japonicum [ 34 ]. DNA vaccine contains a eukaryotic expression vector that could improve protein folding, therefore enable surface-exposed epitopes to be correctly presented and enable post-translational modification [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA vaccine is considered an alternative, even optimal approach because of the simplicity of its manufacturing and distribution, biological stability and cost effectiveness [ 31 ]. DNA vaccines have been shown to induce protective immunity against abroad range of pathogens such as Dengue virus [ 32 ], intracellular protozoan Leishmania major [ 33 ] or helminth parasite Schistosoma japonicum [ 34 ]. DNA vaccine contains a eukaryotic expression vector that could improve protein folding, therefore enable surface-exposed epitopes to be correctly presented and enable post-translational modification [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter study also showed that SjFABP + IL-18 increased the Th1 immune response by producing a higher level of IFNγ and a lower level of IL-4 compared with mice vaccinated only with SjFABP [ 80 ]. Somewhat disappointedly, the Sj14 DNA vaccine, coupled with Sj26GST to form a bivalent DNA-based vaccine, resulted in a reduced level of protective efficacy [ 81 ].…”
Section: Vaccine Candidates For S Japonicummentioning
confidence: 99%
“…To date, several S. japonicum vaccine candidates have been tried [reviewed in Tebeje et al ( 20 )] including a 67 kDa S. japonicum surface protein (Sj67) ( 21 ), the Triose Phosphate Isomerase (SjTPI) ( 22 , 23 ), a Thyroid hormone receptor beta (SjTHRβ) ( 24 ), a S. japonicum fatty acid binding protein (SjFABP) ( 25 , 26 ), a 23-kDa tetraspanin protein (rSjC23DNA) fused to bovine heat shock protein 70 (HSP70) ( 27 ), a 26-kDa parenchymal protein (Sj26GST) ( 28 ), and the 97-kDa protein Paramyosin (Sj97) ( 12 , 29 – 31 ). Several of these, particularly rSJC23DNA, Paramyosin, and SjTPI have shown promise in preliminary protection studies in water buffalo.…”
Section: Introductionmentioning
confidence: 99%